Influence of Two Desensitizer Agents on the Microleakage of Adhesively Luted Ceramic Inlays - Celik, Esra Uzer; Kumbaraci, Nazli; Cal, Ebru; Murat, Turkun (European Journal of Dentistry, 2011)
Objectives: The purpose of this study was to evaluate the effects of two different desensitizers (Hemaseal & Cide and Aqua Prep F) on the microleakage of ceramic inlay restorations luted with adhesive resin cement. Methods: Cylindrical Class V cavities were prepared on the buccal surfaces of thirty extracted human third molars. One of the desensitizers (either Hemaseal&Cide, Advantage Dental Products Inc. or Aqua-Prep F, Bisco) was applied to the cavities. Ten samples were used as controls. Ceramic inlays were fabricated using the heat-pressed glass ceramic technique (IPS Empress II). Inlay restorations were luted using adhesive cement (Variolink II, Ivoclar-Vivadent). The restorations were properly finished, stored in distilled water at 37°C for 24 h and subjected to 1000 thermal cycles. The microleakage scores were examined using a stereomicroscope at the 30x magnification after each sample was stained with 0.5% basic fuchsin. The data were analyzed using Kruskall Wallis and Mann Whitney U tests (P=0.05). Results: Aqua-Prep F samples showed significantly higher microleakage scores at the enamel margins than did the Hemaseal & Cide and control groups (P<.05). Hemaseal & Cide application led to less microleakage than the other groups both at the enamel and dentin margins (P<.05). Conclusions: Hemaseal & Cide desensitizer decreased the microleakage process at the enamel and dentin margins of inlay restorations luted with adhesive luting cement, while Aqua-Prep F increased the leakage scores at the enamel margins. (Eur J Dent 2011;5:77-83)
Keywords: Desensitizers; Microleakage; SEM; Inlay restorations